Sulfated Phenolic Substances: Preparation and Optimized HPLC Analysis - Petrásková, Lucie; Káňová, Kristýna; Brodsky, Katerina; Hetman, Anastasiia; Petránková, Barbora; Pelantová, Helena; Křen, Vladimír; Valentová, Kateřina (International journal of molecular sciences, 2022)
Sulfation is an important reaction in nature, and sulfated phenolic compounds are of interest as standards of mammalian phase II metabolites or pro-drugs. Such standards can be prepared using chemoenzymatic methods with aryl sulfotransferases. The aim of the present work was to obtain a large library of sulfated phenols, phenolic acids, flavonoids, and flavonolignans and optimize their HPLC (high performance liquid chromatography) analysis. Four new sulfates of 2,3,4-trihydroxybenzoic acid, catechol, 4-methylcatechol, and phloroglucinol were prepared and fully characterized using MS (mass spectrometry), 1H, and 13C NMR. The separation was investigated using HPLC with PDA (photodiode-array) detection and a total of 38 standards of phenolics and their sulfates. Different stationary (monolithic C18, C18 Polar, pentafluorophenyl, ZICpHILIC) and mobile phases with or without ammonium acetate buffer were compared. The separation results were strongly dependent on the pH and buffer capacity of the mobile phase. The developed robust HPLC method is suitable for the separation of enzymatic sulfation reaction mixtures of flavonoids, flavonolignans, 2,3-dehydroflavonolignans, phenolic acids, and phenols with PDA detection. Moreover, the method is directly applicable in conjunction with mass detection due to the low flow rate and the absence of phosphate buffer and/or ion-pairing reagents in the mobile phase.
Keywords: Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; HPLC analysis; flavonoids; Desulfitobacterium hafniense; Sulfates; sulfates; Flavonoids; Phenols; polyphenols; Flavonolignans; sírany; phenolic acid; flavonoidy; aryl sulfotransferase; fenoly; flavonolignany